Effect of an ionizing radiation and low temperatures on structural - dynamic state of blood proteins - Zidenko, V. A.; Gatash, S. V.; Gorbenko, G. P. (Biophysical Bulletin, 2018)
The structural changes of such blood proteins as albumin and fibrinogen at the influence of gamma-radiation in doses 18 and 45 Gy and freezing with rates 2000C/min and 10C/min were investigated by the method of quenching of tryptophane fluorescence by acrylamide, Cs+, КJ-. It was determined that such factors influence on structural stiffness of proteins and environment of their chromophores. The comparative characteristic of the influence of gamma-radiation and freezing with different doses and rates is shown. The revealed different directivity of effects in studied proteins is explained by qualitative difference of their native conformation.